Repeatability of Human Intelligence Quotient and its Relationship with Some Trace Elements in Blood Serum - JM Aldahham, Bilal; M. Al-Ani , Louay; M. Mahmood, Huda (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to estimate the repeatability of human intelligence quotient and to find out the relationship between human intelligence and the concentration of Zn, Mg, and Cu in serum. The relationship between Zn, Mg, and Cu concentrations and intelligence was investigated for 102 students at the University of Anbar; their ages were 20-23 years old. Intelligence quotient (IQ) was evaluated using the Raven Matrices Test (RMT). Four ml of blood was withdrawn from the students to determine the concentration of Zn, Mg, and Cu. The obtained data were analyzed by regression analysis. The repeatability estimates of the IQ quotient show low values, which were 0.032 ± 0.19. There were significant and positive relationships between zinc (p< 0.05), magnesium (p < 0.01), and copper (p< 0.05) with IQ. The results of this study participate in building an idea of improving the IQ. Also, this research removes some ambiguity about some essential micronutrients of humans and their relation with intelligence using scientific international ways.